The role of host-country characteristics on subsidiary performance - Syed Ali Fazal; Sazali Abdul Wahab (Universiti Malaysia Kelantan, 2015)
Since the world has evolved as a Global Village, technological innovations has become crucially important for sustaining market competition and gaining competitive edge. Multinational Corporations (MNCs) mostly enjoying technologically advanced positions play vital role in disbursing technological knowledge throughout firms globally. Although numerous studies exist on technology transfer the majority of existing literature addresses the issues related to inter-firm transfer of technology only while the area related to intra-firm transfer of technology has been largely underexposed; study of which is believed to be ideal for fruitful exploration of profitability in technology transfer projects. Using data from MNCs in Malaysia the current study for the very first time would attempt to empirically find the effect of host-country characteristics on the performance of technology transferred by the MNCs and its subsequent influence on subsidiary performance. Findings of this study are expected to contribute both theoretically in the body of knowledge and also in terms of practical implication for policy makers and MNCs and hence enriching the existing literature simultaneously.